12x+3=8x+7

Simple and best practice solution for 12x+3=8x+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12x+3=8x+7 equation:


Simplifying
12x + 3 = 8x + 7

Reorder the terms:
3 + 12x = 8x + 7

Reorder the terms:
3 + 12x = 7 + 8x

Solving
3 + 12x = 7 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
3 + 12x + -8x = 7 + 8x + -8x

Combine like terms: 12x + -8x = 4x
3 + 4x = 7 + 8x + -8x

Combine like terms: 8x + -8x = 0
3 + 4x = 7 + 0
3 + 4x = 7

Add '-3' to each side of the equation.
3 + -3 + 4x = 7 + -3

Combine like terms: 3 + -3 = 0
0 + 4x = 7 + -3
4x = 7 + -3

Combine like terms: 7 + -3 = 4
4x = 4

Divide each side by '4'.
x = 1

Simplifying
x = 1

See similar equations:

| -8p+9+9p=15 | | x^2+14x=900 | | 135+5=140-40 | | 0=x^2-14x+45 | | 5(2a-5b+3c)= | | d^2+12d+36= | | 7x-5=3x+10 | | -3-(-3x)=0 | | 3x+5=4x-40 | | -4-(-3x)=0 | | -2-(-3x)=0 | | 4w^2-28=0 | | y+12y=8 | | 0.2X+27=82 | | -1-(-3x)=0 | | -4(3x+3)=-4(5x-3) | | x+mx+b=0 | | 0=x^2+11x+18 | | 7x+12=0 | | 7c+3=13 | | 0=x^2-11x+18 | | 10x=6x-12 | | u^2-3u-28=0 | | x+3(-1)=0 | | (3x+3)(x+-2)=0 | | -5+x^2=0 | | 5y+6=41 | | 4(x-4)=12 | | -5x+4y=42 | | (x+2)(x+1)(x-1)(x-3)= | | 2.32x=2 | | x(x+1)=x+5 |

Equations solver categories